Deaths and hospitalizations resulting from poisoning by prescription and over-the-counter drugs in Brazil - Fernanda Gross Duarte; Marcelo Neubauer de Paula; Nelzair Araújo Vianna; Maria Conceição Chagas de Almeida; Edson Duarte Moreira Junior (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To estimate the incidence of hospitalizations considering drug intoxication and the mortality of these diseases in Brazil, given trends from 2009 to 2018. METHODS: Data on hospital admissions and deaths come from DATASUS and demographic data from the Brazilian Institute of Geography and Statistics (IBGE). Hospital admissions with Autorização para Internação Hospitalar (AIH - Authorization for Hospital Admission) indicated as a procedure "treatment of intoxication or poisoning due to exposure to drugs and substances for non-drug use" were selected, with only cases of hospitalization due to drug intoxication being analyzed. The incidence of hospitalization and mortality were calculated separately for intoxications caused by medicamentos com prescrição (MRx - prescription drugs) and medicamentos isentos de prescrição (MIP - over-the-counter drugs). Rates were further stratified by sex, age group, and region of residence in Brazil. Trend analysis was performed by generalized linear regression using the Prais-Winsten method. RESULTS: MRx caused most hospitalizations (97%), with mortality approximately 50 times higher when compared to hospitalizations for MIP. The incidence trend in hospitalizations for MRx was stationary and mortality increased during the study period, whereas the trend in mortality and in the incidence of hospitalizations for MIP decreased. CONCLUSIONS: Hospitalizations for drug intoxication, especially those caused by MRx, have a great impact and importance on public health considering that prevention is possible.